2019
DOI: 10.33369/jeet.3.3.377-391
|View full text |Cite
|
Sign up to set email alerts
|

EFL Learners’ Perceptions towards their Self-Efficacy in Learning Public Speaking Course

Abstract: This article reports on EFL learners’ perception towards their self-efficacy in public speaking course. Self-ef?cacy has been de?ned as a person’s perceptions of his or her capabilities to complete a speci?c task with the skills that s/he possesses (Bandura, 1997). Thus, It is important for students to measure their skill in order to improve achievement in public speaking course. This research employed a survey study by means of two data collection techniques; questionnaire and interview. The sample of this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…Nevertheless, in previously conducted research, the results showed that self-efficacy has increased significantly following a public speaking program. Studies focused on the self-efficacy of speaking a foreign language following a public speaking course (Maryam, Febriani & Kurnia, 2019;Paradewari, 2017) or on engineering students who obtained an increase in the level of self-efficacy following a public speaking course (Schuurman et al, 2008). Moreover, according to the principle of vicarious learning postulated by Bandura in 1977, simply witnessing a well-made discourse could serve as a future direction and increase the level of selfefficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in previously conducted research, the results showed that self-efficacy has increased significantly following a public speaking program. Studies focused on the self-efficacy of speaking a foreign language following a public speaking course (Maryam, Febriani & Kurnia, 2019;Paradewari, 2017) or on engineering students who obtained an increase in the level of self-efficacy following a public speaking course (Schuurman et al, 2008). Moreover, according to the principle of vicarious learning postulated by Bandura in 1977, simply witnessing a well-made discourse could serve as a future direction and increase the level of selfefficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Kasunic (2005, p. 3-4) argues that a survey is a data gathering and analysis approach in which respondents answer a question or respond to statements that are developed in advance. According to Cohen and Manion ( 2018), as cited in Nunan (1992, p.140) and (Maryam, et al, 2019), surveys are the most commonly used descriptive method in educational research and can vary in scope from large-scale government investigations to small-scale studies which conducted by a single researcher. In this research, the researcher focuses on a survey about investigating preservice English teachers' perceptions on the use of multimedia in the teaching and learning process.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the speaking performance, self-efficacy supports the EFL (English Foreign Language) learners to be better in speaking performance (Rustandi & Bunga Febriani, 2020). It also formally increases self-confidence and speaking ability and lessens nervousness (Maryam et al, 2019). Similarly, the confidence of the EFL speakers was developed by a positive mindset and goals to face the feedback subject in speaking English (Florensio Wijaya & Laos Mbato, 2020).…”
Section: Increase the Students' Motivationmentioning
confidence: 99%
“…It is a naturally well-prepared topic to persuade the audience. The students prepared the text through research, polished it, outlined it, and practiced it to increase their speech grades (Maryam et al, 2019). Likewise, the students of EFL learners practice speaking by preparing a speech.…”
Section: Prepared Speechmentioning
confidence: 99%